Study of Determination Settlement of Shallow Foundations in Case of sufficient Foundations Load Bearing Capacity in Clay Layers and 2D Modeling by Finite Element Method Case Study: (Ban Donmai Campus, Souphanouvong University) : https://doi.org/10.69692/SUJMRD0901229 - Sitthivong, Phouthamala; Chansavang, Bounsana; Bounxayyavong, Somsanouk; Simmavong, Khongseng; Thavongsy, Boulaphant (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
The purpose of this research study was to study the behavior and Study of determination settlement of shallow foundations in case of sufficient foundations load bearing capacity in clay layer and 2D modeling by Finite Element Method (FEM). The wash boring was performed and the Undisturbed Sample soil was sampled to obtain the basic soil properties in the laboratory according to the 7.5 - 10 m the soil excavation characteristics from the actual construction at the level of excavation from 1 - 1.45 meters, For 1.5 x 1.5 m foundations and 2 x 2 m foundations. In addition, the bearing capacity of the foundation and the soil bearing capacity under the foundation. To analyze the parameters used to evaluate the settlement value and the effect. To analyze the settlement of the various theories and to use the Static Method to analyze the load-bearing capacity of the foundation and to evaluate the Settlement value, The Finite Element Method (FEM) model and the Mohr coulomb soil behavior model was used. The Result for a 1.5 x 1.5 m settlement of shallow foundation with a bearing capacity of 80 Tons. The mean settlement of shallow foundation values ​​for the and Perloff = 6.136 cm. For 2 x 2 m foundations, the bearing capacity of the foundation is 80 Tons. The total settlement values ​​for the Finite Element Method (FEM) = 60 Tons. Perloff's method can receive only 40 Tons of bearing capacity. For a 2 x 2 m foundation, the Bowles, Harr, Christian and Carrier, and Janbu methods = 80 Tons of bearing capacity, while the Perloff method and the FEM method only 40 Tons of bearing capacity.